A construção da fantasia fundamental como limite à Durcherbeitung freudiana: uma contribuição a partir de Lacan - Almeida, Ricardo Monteiro Guedes de (2017)
The purpose of the present study was to investigate the notion of the construction of the fundamental fantasy in Lacan, aiming at a possible articulation with the Freudian concept of Durcharbeitung. Our guiding question was how the construction of the fundamental fantasy imposes itself as a limit to the tireless work of the analysand's perlaboration. We start from the notion that the construction of the fundamental fantasy indicates a limit to the persistent work of the significant articulation, characterized by the Durcharbeitung, as well as an opening for the notion of a finite analysis. To develop this thesis, we mainly cover the works of Jacques Lacan. With this purpose, we limited ourselves to his teachings from 1957 to 1967, a period that goes from Seminar 5: the formations of the unconscious to Seminar 14: the logic of fantasy. In our last chapter, based on Seminar 14, the logic of fantasy, we approached Klein's quadrangle and the way Lacan uses it to represent the route of an analysis. Only then was it possible to address the fundamental fantasy as the subject's deadlock and its role in the route of the analytic process, more specifically in the work of Durcharbeitung. In conclusion, we defend that the fundamental fantasy, associated with the subject's deadlock, represents in the analysis a limit point to the work of Durcharbeitung. We understand that the fundamental fantasy was present both at the point of arrival of the time of understanding and also at the point of departure from the moment of conclusion